Acute Atrial Fibrillation Derived by Single-Doze Fentanyl Transdermal Usage - Gitmez, Mesut; Ekingen, Evren; Yilmaz, Mustafa; Cakmak, Tolga (Derman Medical Publ, 2014)
Fentanyl is a selective and synthetic opiate agonist. Especially in cancer-derived pain treatment fentanyl transdermal usage is preferred. Clinic impacts occur related to several systems derived by fentanyl usage. However, respiratory failure, hypothermia and bradycardia are observed the most. In this article, we aimed at presenting a case which developed atrial fibrillation derived by single-dose fentanyl transdermal usage.
Keywords: Arrhythmia; Atrial Fibrillation; Fentanyl Transdermal